2020
DOI: 10.1038/s41598-020-61729-1
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Candidates for the Treatment of Malassezia pachydermatis -Associated Infections

Abstract: the opportunistic pathogen Malassezia pachydermatis causes bloodstream infections in preterm infants or individuals with immunodeficiency disorders and has been associated with a broad spectrum of diseases in animals such as seborrheic dermatitis, external otitis and fungemia. The current approaches to treat these infections are failing as a consequence of their adverse effects, changes in susceptibility and antifungal resistance. Thus, the identification of novel therapeutic targets against M. pachydermatis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…It is formed by homocitrate synthase due to propionyl-CoA carboxylase deficiency. Homocitrate synthase is considered as a novel therapeutic target of immunologic deficiency syndromes ( Sastoque et al., 2020 ). This study speculated that aurantio-obtusin interfered with homocitric acid by affecting homocitrate synthase, but the relationship between aurantio-obtusin and immune deficiency needed further study.…”
Section: Discussionmentioning
confidence: 99%
“…It is formed by homocitrate synthase due to propionyl-CoA carboxylase deficiency. Homocitrate synthase is considered as a novel therapeutic target of immunologic deficiency syndromes ( Sastoque et al., 2020 ). This study speculated that aurantio-obtusin interfered with homocitric acid by affecting homocitrate synthase, but the relationship between aurantio-obtusin and immune deficiency needed further study.…”
Section: Discussionmentioning
confidence: 99%
“…With increased recognition of azole resistance in Malassezia species, there has also been an expansion in the investigation of alternative treatment approaches, including photodynamic therapy, natural products, antifungal peptides and proteinase inhibitors [ 443 , 454 , 455 , 456 , 457 , 458 , 459 ].…”
Section: Treatment Of Malassezia -Related Diseasesmentioning
confidence: 99%
“…The culture medium used was Sabouraud supplemented with 0,5% Tween 40 and 0,5% Tween 60. Previous studies used this medium and showed adequate growth and easy visual evaluation of the results 11 , 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Lysine is one of these candidates showing yeast growth inhibition in vitro. However, further studies are required 11 . Other candidates include essential oils from different plants 12 .…”
mentioning
confidence: 99%